4(7t+1)-10=t-(t+5)

Simple and best practice solution for 4(7t+1)-10=t-(t+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(7t+1)-10=t-(t+5) equation:


Simplifying
4(7t + 1) + -10 = t + -1(t + 5)

Reorder the terms:
4(1 + 7t) + -10 = t + -1(t + 5)
(1 * 4 + 7t * 4) + -10 = t + -1(t + 5)
(4 + 28t) + -10 = t + -1(t + 5)

Reorder the terms:
4 + -10 + 28t = t + -1(t + 5)

Combine like terms: 4 + -10 = -6
-6 + 28t = t + -1(t + 5)

Reorder the terms:
-6 + 28t = t + -1(5 + t)
-6 + 28t = t + (5 * -1 + t * -1)
-6 + 28t = t + (-5 + -1t)

Reorder the terms:
-6 + 28t = -5 + t + -1t

Combine like terms: t + -1t = 0
-6 + 28t = -5 + 0
-6 + 28t = -5

Solving
-6 + 28t = -5

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 28t = -5 + 6

Combine like terms: -6 + 6 = 0
0 + 28t = -5 + 6
28t = -5 + 6

Combine like terms: -5 + 6 = 1
28t = 1

Divide each side by '28'.
t = 0.03571428571

Simplifying
t = 0.03571428571

See similar equations:

| 6(y+5)=-36 | | 3x-16=86 | | (2x^7-8y^8)(4x^6+6y^2)= | | 4n-7=45 | | 28+9x=258 | | 28+9=258 | | N+13.7=-6.3 | | 7u+4=4-7u | | 8-7n=34 | | 2k^2-7k=0 | | 5xm=d | | 7n+8=34 | | 0(t)=3.25t^2+-75 | | 6x-(3y)=15 | | 34-8=7n | | s(t)=3.25t^2-75 | | 4x^3-12x+8= | | 4w+4=6w+14 | | 5(7p-5)-[2(2p-3)+4]= | | 60-3(9-5)3= | | In(x)+In(x-2)=In(3) | | 5-9-7-1= | | 3x(-2x-7)-2y=9 | | 12-2y=8y+4 | | -6(2y-1)=3.6 | | 25.0139-7.481x=-1.1(x-8) | | 4x=15-5y | | -9p+21+16p=5(p+4)+3 | | 2x-11=38+9x | | -2m-6+8m=-4m-2+10m | | 6.5(1+0.495*1.2)=5.114+4.3*1.2 | | 3p+3(p+2)=6p+2 |

Equations solver categories